The Influence of Ibn Sina's Islamic Educational Thought on the Formation of the Character of Generation Alpha - Alwi Mubarok Assidiq; Betty Mauli Rosa Bustam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the relevance of Ibn Sina's educational philosophy in shaping the character of Generation Alpha. Ibn Sina's comprehensive educational thinking, including goals, curriculum, teaching methods, and the role of educators, is still relevant today. Generation Alpha, born after 2010, faces challenges in character development, often exhibiting individualistic behavior and reduced empathy due to being too immersed in digital technology. This study investigates how Ibn Sina's concepts can be integrated into character education for Generation Alpha, which aims to cultivate individuals who are intellectually and spiritually balanced. The findings aim to provide insight into educational approaches that incorporate moral and spiritual values that are essential for the character development of Generation Alpha.